Gas‐liquid mass transfer behavior in a surface‐aerated vessel stirred by a novel long‐short blades agitator. Issue 4 (28th November 2015) - Luo, Peicheng; Wu, Jun; Pan, Xiang; Zhang, Yueqiao; Wu, Hua
Abstract : For a recently developed long‐short blades (LSB) agitator, its critical rotational speed for the onset of gas entrainment, power number, and gas‐liquid mass transfer behavior in the case of surface aeration is investigated. The effect of the LSB configurations and the liquid level on the agitator performance has been studied in details. The obtained results clearly show several advantages of the LSB agitator in gas‐liquid mass transfer with respect to the agitators in the literature. It is found that its gas‐liquid volumetric mass‐transfer coefficient at a given specific power can be several times larger than those shown in the literature. It can also avoid decrease in the gas‐liquid mass transfer rate as the liquid level increases. In addition, the bubble distribution in the system is more uniform with respect to conventional agitators, resulting from better distribution of the dissipated energy for the LSB agitator. © 2015 American Institute of Chemical Engineers AIChE J, 62: 1322–1330, 2016